New technology-based firms in the new millenium. Vol. 7 - Oakey, R. P. (Emerald, 2009)
The research and policy evaluations presented in these papers represent a uniquely valuable evolving record of policy and research on high technology small firms through many changes in economic conditions and government policy approaches over more the a decade and a half. Specific issues in the book series cover many of the key industrial development policies adopted by developed, and developing, national governments since the early 1990s including, for example, writings on policy and practice concerning science parks, incubators, academic enterprise, industrial networking and the role of clusters in nurturing high technology small firms formation and growth. In particular, the on-going problem of early stage high technology funding has been a theme of constant concern since1993, and because it remains resistant to amelioration, will endure into the future. Both the conference and the ensuing book series represent a pre-eminent vehicle for all the major international researchers concerned with high technology small firms to present their work to each other and the wider public.
Keywords: Business & Economics -- Industries -- Computer Industry.; Information technology industries.; Industrial applications of scientific research & technological innovation.; Industrial policy.; High technology.; New business enterprises.; elektronické knihy; electronic books